Pengaruh Hasil Belajar Praktik Terhadap Keberhasilan Praktik Kerja Industri Siswa Kelas XII Jurusan Multimedia UPT SMK Negeri 2 Pare-pare - Anwar, Handayani; Muh. Yusuf Mappease; Ruslan (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
This study aims to determine students' practical learning outcomes, the success rate of students' industrial work practices, and also the positive and significant influence of practical learning outcomes on the success of students' industrial work practices. The number of samples was 52 students of class XII UPT SMK Negeri 2 Parepare. Data collection techniques using questionnaires and documentation. The data analysis technique was carried out using descriptive analysis techniques, simple linear regression analysis techniques using the SPSS program. The results showed that based on the results of the frequency distribution of student learning outcomes at UPT SMK Negeri 2 Parepare were in the complete category as many as 52 students with a percentage of 100%, the results of the frequency distribution data for the success of students' industrial work practices in printing graphic design subjects were in the category high and this research proves that there is a positive and significant effect on practical learning outcomes (X) on the success of students' industrial work practices (Y).